Outcome of haematopoietic stem cell transplantation in dyskeratosis congenita - Fioredda, Francesca; Iacobelli, Simona; Korthof, Elisabeth T; Knol, Cora; van Biezen, Anja; Bresters, Dorine; Veys, Paul; Yoshimi, Ayami; Fagioli, Franca; Mats, Brune; Zecca, Marco; Faraci, Maura; et al. (British journal of haematology, 2018)
Dyskeratosis congenita (DC) is a genetic multisystem disorder with frequent involvement of the bone marrow. Haematopoietic stem cell transplantation (HSCT) is the only definitive cure to restore haematopoiesis, even though it cannot correct other organ dysfunctions. We collected data on the outcome of HSCT in the largest cohort of DC (n = 94) patients ever studied. Overall survival (OS) and event-free survival (EFS) at 3 years after HSCT were 66% and 62%, respectively. Multivariate analysis showed better outcomes in patients aged less than 20 years and in patients transplanted from a matched, rather than a mismatched, donor. OS and EFS curves tended to decline over time. Early lethal events were infections, whereas organ damage and secondary malignancies appeared afterwards, even a decade after HSCT. A non-myeloablative conditioning regimen appeared to be most advisable. Organ impairment present before HSCT seemed to favour the development of chronic graft-versus-host disease and T-B immune deficiency appeared to enhance pulmonary fibrosis. According to the present data, HSCT in DC is indicated in cases of progressive marrow failure, whereas in patients with pre-existing organ damage, this should be carefully evaluated. Further efforts to investigate treatment alternatives to HSCT should be encouraged.
Keywords: dyskeratosis congenita; transplantace hematopoetických kmenových buněk; Humans; haematopoietic stem cell transplantation; analýza přežití; Graft vs Host Disease; nemoci kostní dřeně; Hematopoietic Stem Cell Transplantation; Female; příprava pacienta k transplantaci; dospělí; mladý dospělý; věkové faktory; výsledek terapie; Tissue Donors; lidé; Bone Marrow Diseases; Survival Analysis; Adult; dárci tkání; ženské pohlaví; Male; nemoc štěpu proti hostiteli; Pulmonary Fibrosis; Treatment Outcome; Transplantation Conditioning; Dyskeratosis Congenita; Young Adult; Age Factors; mužské pohlaví; plicní fibróza; bone marrow failure